The application of different orientation of orthotropic composite beam - Abdellatif, Elaakili; Bekkaye merrimi, El (Journal of Biomaterials, 2023)
In the present document, the dynamic analysis of isotropic materials applied to the laminated composite beam has been studied to improve the simplification of the homogenization process of heterogeneous composite materials.12 This study is based on the conventional stratified theory of Von Karman's formulation and the kinetic energy of Euler Bernoulli developed through displacement relationships. The model used in this study to explain the problem of non-linear geometry in the free vibration applied of laminated beam is based on the Hamilton's principle for solving the motion equation and determining the frequency of the reaction of the rolled beam. The numerical of the symmetric an asymmetric material gives a good idea of the behaviour of the orthotropic materials, and to minimize the problem of many areas used these materials such as: dental medicine, aeronautical, aerospace, because they have a good strength, high rigidity.23 The comparison between the different lay up may give greater importance to this study and open the search to simplify the problem of non linear geometry and give a good result about the older other published. For instance the application of medicine,the researcher has to decode the compatibility of the human body with new materials,and to minimize the problem of deterioration,The comparison with different lay up give more interesting by the mechanical engineering and the researcher's to give the solution of no linear problem and optimize the composite material’s to adaptation with problem study.4
Keywords: orthotropic composite beam; application; lay up.